Insurance against aggregate shocks - Takuma Kunieda; Akihisa Shibata (Osaka University, Institute of Social and Economic Research (ISER), 2024)
Although many studies in macroeconomics have examined the role of insurance in the presence of income risk, whether aggregate shocks are insurable has not been sufficiently investigated. We present a simple two-period general equilibrium model to show the conditions under which insurance against aggregate shocks works in an economy with constant-elasticity-substitution (CES) production technology and the Greenwood-Hercowitz-Huffman (GHH) utility function (Greenwood et al.,1988). Our theoretical investigation clarifies that only when agents are heterogeneous in their ability or initial wealth can aggregate shocks be insurable. From our quantitative investigation, we find that (i) agents with lower ability enjoy greater welfare improvement from insurance, and as agents' ability increases, the welfare improvement diminishes, (ii) agents enjoy greater welfare improvement when the damage from disasters is more severe and when the frequency of disasters is greater, and (iii) although the welfare improvement increases as agents' initial wealth increases, the impact of a difference in agents' initial wealth on the difference in the contribution of insurance is very moderate.
Keywords: D52; G12; 330; aggregate shocks; heterogeneous agents; state-contingent claims; incomplete market